Unusual Presentation of a Metastatic Lymph Node from Giant Phyllodes Tumour of Breast– A Case Report - Abraham, Sherry; Solomon, Patricia; B, Rajesh; B, Selvamani (Archives of Clinical and Medical Case Reports, 2020)
Background: Phyllodes tumours(PTs) of breast are rare fibroepithelial neoplasms which constitute 0.3% to 0.5% of female breast tumours. Malignant PTs usually develop haematogenous spread and only <1% of the patients with PT have lymph node metastasis. Case Presentation: We report a 38 year old premenopausal lady who presented with a progressive right breast lump with intermittent pain of one year duration. She had similar history two years ago and was diagnosed with phyllodes tumour for which she underwent lumpectomy in hometown. Local examination of right breast revealed a 20 × 15cm sized lump of variegated consistency involving all the quadrants and two hard, mobile lymph nodes of size 2.5cm were palpable in the right axilla. Trucut biopsy of the right breast lump showed compressed ducts lined by benign bilayered cuboidal epithelium with stromal nuclear atypia and occasional mitotic activity suggestive of phyllodes tumour of aggressive behavior. She underwent modified radical mastectomy with right axillary lymph node clearance. Histopathology of the specimen was suggestive of malignant phyllodes tumour and seven of 11 axillary lymph nodes contained metastatic disease. She received 4 cycles of adjuvant chemotherapy with single agent Doxorubicin and radiotherapy to the chest wall following the same. She was advised to be on follow up. Four months later she presented with two weeks history of dyspnea and was found to have bilateral pleural effusion, pericardial effusion, tricuspid ball valve thrombus and acute submassive pulmonary embolism. Though effusions were thought to be secondary to malignancy, cytology did not prove the same. She succumbed to her illness within 72 hours of admission to emergency room. Conclusion: Malignant phyllodes tumour is a rare entity which mimics benign neoplasm clinically, but behave like sarcomas with poor prognosis and haem